Prevalence of Cognitive Impairment and Depression among a Population Aged over 60 Years in the Metropolitan Area of Guadalajara, Mexico - Ortiz, Genaro G. (Hindawi Publishing Corporation, 2012)
Background. Cognitive impairment is an important clinical issue among elderly patients with depression and has a more complex etiology because of the variable rate of neurodegenerative changes associated with depression. The aim of the present work was to examine the prevalence of cognitive impairment and depression in a representative sample of adults aged ≥60 years. Methods. The presented work was a cross-sectional study on the prevalence of cognitive impairment and depression. Door-to-door interview technique was assigned in condition with multistage probability random sampling to obtain subjects that represent a population of the Guadalajara metropolitan area (GMA), Mexico. Cognitive function and depression were assessed by applying standardized Mini-Mental State Examination of Folstein (MMSE) and the Geriatric Depression Scale (GDS), respectively. Results. Prevalence of cognitive impairment was 13.8% (14.5% women, 12.6% men); no significant differences by gender and retired or pensioner were found. Prevalence of depression was 29.1% (33.6% women, 21.1% men); no significant differences by retired or pensioner were found. Cognitive impairment was associated with depression (OR  =  3.26, CI 95%, 2.31–4.60). Prevalence of cognitive impairment and depression is associated with: being woman, only in depression being older than 75 years being married, and a low level of education. Conclusion. Cognitive impairment and depression are highly correlated in adults aged ≥60.